Dinamika Kebijakan Pembelajaran Daring di Era Pandemi Covid-19 - Yenik Pujowati (LPPM Universitas Trunojoyo Madura, 2021)
The purpose of the research is to find out how the dynamics of online learning policies are in the Covid-19 pandemic era. The increasingly widespread spread of the Covid-19 pandemic has become one of the inhibiting factors in the world of education. The government's policy is to implement the Work from Home work pattern, namely all teaching and learning activities must be carried out at home, online learning to prevent the spread of Covid-19. The research method is a qualitative research, this research uses the library method, namely tracing documents, reports such as; books, journals, proceedings, articles, activity reports, news media and other written sources. Online learning activities can not be separated from problems such as; limited facilities, cultural changes, family support, not all students have laptops, cellphones. Applications that are often used in online learning such as; zoom, google classroom, teacher room and whatssap group. The researchers' conclusion; The dynamics of online learning policies in the Covid-19 pandemic era can be carried out well, according to creativity, lecturers, teachers in providing material and practice questions. The weakness of online learning such as internet network factors are uneven, not all proficient use of technology applications, lack of cultural understanding of digital media communication, cost limitations (quota internet).